ANALISIS KESULITAN GURU MEMBELAJARKAN MATERI FOTOSINTESIS DI KELAS V SD - Hasibuan, Vivi Uvaira (Jurnal Pendidikan Guru, 2017)
This research was conducted in SDN Se-District of Perbaungan which aims to determine (1) the level of difficulty of teachers in teaching photosynthesismaterial in class V SD Se-District of Perbaungan; and (2) efforts to overcome the difficulties school teachers in teaching photosynthesis material in class V SD Se-District of Perbaungan. The population in this study were all teachers of Class V SDN Se-District of Perbaungan by 43 SDN while the study sample of 40 people classroom teachers from 23 schools SDN Se-District of Perbaungan. The instruments used consist of observation sheets, questionnaires / questionnaire and interview. The results showed that: (1) the level of difficulty Perbaungan sub-district teachers in teaching on the photosynthesismaterial were moderate (59.918%); and (2) efforts to overcome the difficulties school teachers in teaching photosynthesismaterial in class V SD Se-District of Perbaungan include providing training as much as 1 school (4.35%), requiring teachers to follow KKG as much as 1 school (4.35% ), for the moment SDN still difficulties in organizing teacher reference books let alone provide practice tools as much as 4 schools (17.39%), seek to practice using simple tools as much as 4 schools (17.39%), set aside a budget BOS funds as much as 4 schools (17.39%), holding a committee meeting to seek help from the parents of students in 1 school (4.35%), complementary practice tools as much as 2 schools (8.70%), reported to the Office Sub-district for help with practical tools as much as 4 schools (17.39%), and the rest did not respond as much as 2 schools (8.70%).